2003
DOI: 10.1046/j.1440-6055.2003.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Ants as egg predators of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) in Australian cotton crops

Abstract: Helicoverpa armigera is a major pest of Australian cotton crops. To assess the impact of ant predation on H. armigera populations, the behaviour of four common ant taxa was observed in cotton crops in northern New South Wales over the 1999-2000 and 2001-02 seasons. Areas of cotton were artificially stocked with H. armigera eggs prior to observation. Pheidole spp. were the most frequently observed ants within the crop canopy in 1999-2000 and took the most H. armigera eggs. Iridomyrmex spp. were more frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…This may be explained by the presence of natural enemies of these pests in the experimental plots. For instance, Chrysopids and ant species, which are known as the most important predators of H. armigera (Alavo, 2006;Mansfield, Elias, & Lytton-Hitchins, 2003;Romeis & Shanower, 1996;van den Berg, Cock, & Oduor, 1997;van den Berg & Cock, 1993, 1995, were occasionally encountered in the plots. We considered that the presence of these beneficial organisms in the plots was due to the fact that these plots have not been treated with any chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the presence of natural enemies of these pests in the experimental plots. For instance, Chrysopids and ant species, which are known as the most important predators of H. armigera (Alavo, 2006;Mansfield, Elias, & Lytton-Hitchins, 2003;Romeis & Shanower, 1996;van den Berg, Cock, & Oduor, 1997;van den Berg & Cock, 1993, 1995, were occasionally encountered in the plots. We considered that the presence of these beneficial organisms in the plots was due to the fact that these plots have not been treated with any chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…The ants of the genus Odontomachus are generalist predators of the small invertebrates and can be found foraging on the soil surface at day and night, as well as in low vegetation and tree trunks (Briese and Macauley, 1981). In a study on the impact of the ant predation on Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) eggs in the cotton monoculture in Australia, Mansfield et al (2003) found that most eggs were attacked by the ants belonging to the genus Pheidole. Species of the genus Solenopsis are the most abundant group of the predators in the agroecosystems, therefore are important predators of a wide variety of the insects, including the pests of several crops (Eubanks, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies on the ant communities in the tropics were conducted in the natural ecosystems, although the evidence of similar ant functions in the agroecosystems can be found, particularly among the communities of the insects considered pests (Samways, 1983;Mansfield et al, 2003;Rossi and Fowler, 2004) or weeds (Risch and Carroll, 1982). The studies conducted in the Dourados region (MS, Brazil) showed the genera of Pheidole, Solenopsis, Dorymyrmex and Ectatomma as the insect predators in soybean (Fernandes et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…and, to a lesser extent, Iridomyrmex spp. are predators of the cotton bollworm Helicoverpa armigera, but agricultural practices limit their effectiveness as controls (Mansfield et al 2003). Iridomyrmex spp.…”
Section: Ant Defence Of Plants Without Rewardsmentioning
confidence: 99%